Androgen receptor dynamics in prostate cancer: from disease progression to treatment resistance - Li, Caihong; Cheng, Dongkai; Li, Peng (Frontiers in Oncology, 2025)
Prostate cancer is the most common cancer among men worldwide, especially in those over 65, and is a leading cause of cancer-related mortality. The disease typically advances from an androgen-dependent state to castration-resistant prostate cancer (CRPC), which poses significant treatment challenges. The androgen receptor (AR) on the X chromosome is a central driver in this process, activating genes that govern proliferation and survival. Mutations and amplifications of the AR are closely associated with disease progression and treatment resistance. While traditional therapies such as androgen deprivation therapy (ADT) and AR antagonists like enzalutamide have been effective, resistance persists due to reactivation of AR signaling through mechanisms like ligand-independent activation. Recent research highlights the role of epigenetic modifications in enhancing AR activity and drug resistance. The tumor microenvironment, particularly interactions with cancer-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs), further complicates treatment by promoting aggressive tumor behavior and immune evasion. Future directions include developing next-generation AR antagonists, identifying AR-related biomarkers for personalized therapy, and exploring combinations with immune checkpoint inhibitors. Additionally, basal cell-lumen-derived organoids provide innovative models that can enhance understanding and treatment strategies in prostate cancer.